Residential construction law (London [England] : HART PUBLISHING, 2021)
"This is the first book to offer a systematic and analytical overview of the legal framework for residential construction. In doing so, the book addresses two fundamental questions: Prevention: What assurances can the law give buyers (and later owners and occupiers) of homes that construction work ? from building of a complete home to adding an extension or replacing a shower unit ? will comply with minimum standards of design, safety and build quality? Cure: What forms of redress - from whom, and by what route - can residents expect, when, often long after completion of construction, they discover defects? The resulting problems pose some big and difficult questions of principle and policy about standards, rights and remedies, which in turn concern justice more generally. This book addresses these key issues in a comparative context across the United Kingdom, Ireland, Australia and New Zealand. It is both an accessible guide to the existing law for residents and construction professionals (and their legal advisers), and charts a course to further, meaningful reforms of the legal landscape for residential construction around the world. The book's two co-authors, Philip Britton and Matthew Bell, have taught in the field in the UK, Australia and New Zealand and both have been active in legal practice, as have the book's two specialist contributors, Deirdre Ní Fhloinn and Kim Vernau."--
1. Introduction -- 2. Residential Construction: Defects in Context -- 3. Regulation of Residential Construction -- 4. Contract Law in Residential Construction -- 5. Beyond Contract: Other Rights of Legal Action -- 6. Consumer Protection: Other Forms -- 7. Insurance and Third-Party Warranties -- 8. Inspections in Residential Construction -- 9. Pathways to Individual Redress -- 10. Time-Limits for Consumer Action -- 11. Multi-Unit Developments -- 12. Conclusions.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Construction & engineering law; Electronic books